Implementation of multidisciplinary reflective rounds within a children's hospital before and during the COVID‐19 pandemic. (15th February 2021) - Baker, Jonathan; Savage, Amy; Pendleton, Shannon; Bate, Jessica M
Abstract : Aim: Regular reflective practice within a large group setting has been shown to reduce levels of burnout in healthcare professionals. We describe how regular reflective rounds were designed and implemented within an existing educational program at a UK children's hospital and report on the feedback received from participants. Methods: Eight face‐to‐face reflective rounds took place in Southampton Children's Hospital, UK, from September 2017 to February 2020 with a further virtual round in July 2020 during the COVID‐19 pandemic. Each round was facilitated by a clinical psychologist and consultant. For each round, up to three volunteer panellists from different staff groups were invited to share their personal experiences on a pre‐selected subject to the large group. The group would then contribute to the discussion by offering their own reflections. Feedback forms were distributed to attendees and collated. Results: Eight rounds were held with mean attendance of 32 (range 19–47). Across the eight rounds, the total attendance was 256 staff members. The virtual round had 20 participants. Feedback was received from 202 participants. The majority (98%) would recommend the rounds to colleagues with 64 participants (32%) rating the rounds as 'exceptional' and 91 (45%) as 'excellent'. The virtual round received similar positive feedback. Conclusion: Large group reflective practice can be implemented within an existing regular educational program. Rounds have been well received by participants and are likely to be of relevance and value to other healthcare groups. The rounds can also be delivered effectively virtually, which may increase participation.